Modeling and Control of Standalone Direct-Driven PMSG WECS for Grid Compatibility at Varying Wind Speeds - Shilpa Mishra; S Chatterji; Shimi S.L.; Sandeep Shukla (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Wind energy is one of the most available and exploitable forms of renewable energy. Variable speed PMSG based Wind Energy Conversion System (WECS) offers many advantages compared to the fixed speed squirrel cage induction generators such as improved stator output operation at better power factor, no maintenance cost for gear box (as it is direct-driven) reduction in weight and losses, higher efficiency and ability to run at low speeds. The elimination of the gear box and brushes can enhance the efficiency of wind turbine by 10%. In this paper a Permanent Magnet Synchronous Generator (PMSG) is modeled whose stator is connected to the constant single phase load (in place of grid) through AC/DC thyristors based rectifier followed by capacitor (dc-link) and DC/DC converter control. Overall arrangement provides constant output to connected load if applied with proper controlling techniques. Hence this proposed wind generation system design can be extended for grid connection also via DC/AC inverter control. Results are simulated and verified in MATLAB/Simulink platform at constant rated (12m/s) and varying (stepped) wind speed for smooth and constant output voltage. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7097